Cytological and colposcopic evaluation of abnormal cervix - Beg, Ayesha; Islam, Mohammad Aminul; Roy, Nibedita; Jahan, Khurshida; Yasmin, Sabina; Ansari, Nazma Parvin; Nahar, Kamrun (Community Based Medical Journal, 2019)
The second most common cancer among women worldwide is cancer of the cervix commonly develop due to abnormal cervix. To evaluate abnormal cervix by cytology and colposcopy, a prospective study was undertaken among 100 women attending at the colposcopy clinic in Mymensingh Medical College Hospital (MMCH) from January 2008 to July 2008. Cytological and colposcopic evaluation were done in all the patients attending the colposcopy clinic with various complaints like per vaginal discharge, post-coital bleeding, dyspareunia, irregular per vaginal bleeding, backache and abnormal cervix on examination. A biopsy was taken from 53 cases of colposcopically abnormal or clinically doubtful cervices. Cytology and colposcopy findings were compared with the histological results. Study results revealed that 26 apparently healthy cervices in naked eye examination showed abnormal cytology in 8 cases and premalignant and malignant changes was seen in 9 among colposcopically abnormal 11 cases. Among the 40 cases of ectropion, abnormal cytology found in 11 and premalignant and malignant changes in 13 cases. In 11 cases of nabothion cyst, 4 had abnormal cytology and premalignant changes in 2 cases. Among 10 erythema cases, 3 showed abnormal cytology and 6 showed premalignant and malignant changes. One ulcer case revealed malignancy on cytology, colposcopy and histopathology. The other 12 cases, abnormal cytology found in 7, premalignant and malignant changes found in 8. On cytological examination, abnormal cytology found in 34 cases, among these 26 revealed premalignant and malignant on biopsy report. Out of 66 negative cytological smear cases, 23 colposcopically positive and biopsy showed 13 cases as premalignant and malignant. So, 13% cases of premalignant and malignant lesion may be overlooked if cytology alone was used for screening. This study revealed that colposcopy examination significantly reduces false negative cytology. Results of this study concluded that combined procedures enhance diagnostic accuracy. CBMJ 2019 January: vol. 08 no. 01 P: 3-11